2021
DOI: 10.3390/nano11081990
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy/Ionic Liquid-Modified Mica Nanocomposites: Network Formation–Network Degradation Correlation

Abstract: We synthesized pristine mica (Mica) and N-octadecyl-N’-octadecyl imidazolium iodide (IM) modified mica (Mica-IM), characterized it, and applied it at 0.1–5.0 wt.% loading to prepare epoxy nanocomposites. Dynamic differential scanning calorimetry (DSC) was carried out for the analysis of the cure potential and kinetics of epoxy/Mica and epoxy/Mica-IM curing reaction with amine curing agents at low loading of 0.1 wt.% to avoid particle aggregation. The dimensionless Cure Index (CI) was used for qualitative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…The data reported in Table 2 and Figure S5 show that the parameters were not significantly affected by the introduction of mica fillers, in agreement with the data reported in the literature [ 60 , 61 ], where mica was less active compared with silica and CaCO 3 toward thermal decomposition. As for residue values at 700 °C ( Figure S6 ), a linear positive trend was found within the composition range for both Mica 10 and Mica 45 nanocomposites, in agreement with the consideration that by increasing the amount of inorganic filler, the final residue made of char and filler must increase.…”
Section: Resultssupporting
confidence: 90%
“…The data reported in Table 2 and Figure S5 show that the parameters were not significantly affected by the introduction of mica fillers, in agreement with the data reported in the literature [ 60 , 61 ], where mica was less active compared with silica and CaCO 3 toward thermal decomposition. As for residue values at 700 °C ( Figure S6 ), a linear positive trend was found within the composition range for both Mica 10 and Mica 45 nanocomposites, in agreement with the consideration that by increasing the amount of inorganic filler, the final residue made of char and filler must increase.…”
Section: Resultssupporting
confidence: 90%
“…However, there is no mention of the effect of the synergistic cross-linking effect of flame retardants and inorganic compounds on flame retardant properties. Jouyandeh et al 40 synthesized pristine mica (Mica) and N -octadecyl- N ′-octadecyl imidazolium iodide (IM) modified mica (Mica-IM) and characterized it used. The results indicated that the kinetics of the network formation and network degradation were correlated to demonstrate how molecular-level transformations can be viewed semi-experimentally, but the synergistic cross-linking of additives is not mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…By adding CNTs to the formulation, a significant increase can be observed in the decomposition temperature as the decomposition initiation temperature raised from 260 to 340 C. Addition of CNTs in polymer matrix led to increases in all of the T IDT , T max , and ash content (Table 9). The state of nanotube dispersion within the polymer matrix may give useful insights into the thermal degradation behavior, [48][49][50][51] which reveal good distribution of CNTs through the polymer matrix. As per Table 9, there was a rise in ash content by adding CNTs in the system because of the very high thermal stability of the CNTs.…”
Section: Thermal Stability Of Polythioether Elastomersmentioning
confidence: 99%